2002
DOI: 10.1081/erc-120015051
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Effects of Neonatal Hypothyroidism on Wistar Rat Spermatogenesis

Abstract: The effect of neonatal hypothyroidism on spermatogenesis was studied in Wistar rats of different age groups. Hypothyroidism was induced in newborn male rats from day one postpartum up to day 60 postpartum by daily administration of 0.05% methimazole (MMI) to the nursing mothers or directly through drinking water. The animals were killed at days 10, 15, 30, 40, and 60 postpartum, blood plasma was collected, and testes, epididymides, prostates, and seminal vesicles were separated and weighed. Testes were fixed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 40 publications
3
17
0
1
Order By: Relevance
“…In addition to the histological changes, reduced serum testosterone levels were observed in both the rat models. Accordingly, prolonged hypothyroidism induced in rats by either propyl-2-thiouracyl or methimazole treatment was also shown to arrest proliferation and differentiation of germ cells, resulting in a significant decrease in germ cell number and in the percentage of live sperm in the epididymis (Maran and Aruldhas, 2002;Sahoo et al, 2007).…”
Section: Thyroid Hormone and The Adult Testismentioning
confidence: 96%
See 1 more Smart Citation
“…In addition to the histological changes, reduced serum testosterone levels were observed in both the rat models. Accordingly, prolonged hypothyroidism induced in rats by either propyl-2-thiouracyl or methimazole treatment was also shown to arrest proliferation and differentiation of germ cells, resulting in a significant decrease in germ cell number and in the percentage of live sperm in the epididymis (Maran and Aruldhas, 2002;Sahoo et al, 2007).…”
Section: Thyroid Hormone and The Adult Testismentioning
confidence: 96%
“…For instance, TRa1 expression was very high in Sertoli cell nuclei during their proliferative phase, from postnatal days 0 to 15, and subsequently declined markedly with the cessation of proliferation, remaining very low in adulthood. Interestingly, around postnatal day 15, TRa1 was found to be expressed in spermatogenic germ cells, from intermediate spermatogonia to mid-cycle pachytene spermatocytes, and also in Sakai et al, 2004Oncu et al, 2004Maran and Aruldhas, 2002 residual bodies being phagocytosed by Sertoli cells. Functional TR isoforms were also identified in the interstitial compartment of the immature testis, although it was not clear, at that point, in which specific cell types they were expressed (Buzzard et al, 2000).…”
Section: The Ontogeny Of Thyroid Hormone Nuclear Receptors In Testismentioning
confidence: 98%
“…Also, it significantly decreased serum T 4 level. Maran and Aruldhas [24] reported that daily administration of 0.05% methimazole to the nursing mothers induced many changes in newborn male rats; significantly reduced seminiferous tubules diameter, the proliferation and differentiation of germ cells were arrested and their number were decreased.…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, THs have been shown to regulate Sertoli cell proliferation leading to changes in testis development and, subsequently, sperm production after sexual maturity (Cooke et al 1991, Francavilla et al 1991, Maran & Arudhas 2002. The effects of THs on the mammalian testis appear mediated in part via TR-regulated pathways, since knockout of tra1 leads to elevated Sertoli cell number, increased testis mass, and heightened daily sperm production (Holsberger et al 2005).…”
Section: Discussionmentioning
confidence: 99%